PENINGKATAN KUALITAS KESEHATAN MASYARAKAT DI DESA POTRONAYAN KECAMATAN NOGOSARI MELALUI PELAYANAN PENGOBATAN GRATIS: IMPROVING THE QUALITY OF PUBLIC HEALTH IN POTRONAYAN VILLAGE NOGOSARI DISTRICT THROUGH FREE TREATMENT SERVICES - Novita Sari, Erlinda (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2024)
Aging is a natural phase in life, namely the body tends to experience and accumulate changes over time, and these changes are usually degenerative. Potronayan Village is one of the villages in Nogosari District, Boyolali, Central Java. Degenerative diseases are health conditions that cause tissues or organs to deteriorate over time, such as hypertension, diabetes, cholesterol, gout, and so on. Therefore, the aim of this community service activity is to provide health facilities for the community in the form of treatment, doctor consultations, communication and information as well as drug counseling and drug services by pharmacy students free of charge. This service activity is carried out using the method of checking health and administering medication accompanied by treatment counseling. The result of this activity is improved health of the people of Potronayan village. Through this activity, people, especially in Potronayan village, can have good quality health after free treatment.